Periodic behaviour in ground-level environmental radioactivity: fingerprints of solar activity?. (31st May 2018) - Babić, Dinko; Senčar, Jasminka
Abstract : Long-term data on ground-level environmental radioactivity are analysed, these referring to daily records of the total β activity in air and absorbed dose rate between 1976 and 2016 in Zagreb, Croatia. A Fourier analysis of these two datasets reveals a periodic behaviour with numerous periods ranging from approximately four months to roughly 21 years. Ninety per cent of the periods agree remarkably well with known periodicities in solar activity throughout solar cycles 21–24, which suggests that the observed modulations were most probably caused by variations in the cosmogenic radionuclide production in the upper atmosphere. Hence, one can extract the fine structure of solar activity from environmental radioactivity monitoring data, which implies that it could be possible to supplement the existing information on the exposure of Earth to cosmic rays by analysing results from radioactivity monitoring stations all over the world. These datasets cover Earth densely due to the existence of a global radioecological network and are complementary to those resulting from dedicated cosmic ray detection experiments. Because of that, such analyses might possibly lead to new findings.